Microwave Assisted One Pot Synthesis of 3,4-Dihydropyrano[c]chromene Derivatives using [Emim]OH Ionic Liquid as Novel Catalyst - Bhahat, D.S.; Pande, S.G.; Katariya, M.V.; Pawar, R.P.; Kendrekar, P.S. (Asian Journal of Chemistry, 2019)
One-pot efficient protocol to the synthesis of 2-amino-5-oxo-4,5-dihydropyrano(3,2-c)chromene-3-carbonitrile derivatives via condensation of various aryl aldehydes, dicyanomethane and 4-hydroxycoumarin in presence of Emim hydroxide as an excellent homogeneous liquid catalyst. The key advantages of this methodology are mild reaction conditions, novel catalyst, short reaction time, eco-friendly, easy work-up procedure and high yield of isolation of derivatives.
Published Article
Keywords: Microwave Assisted; [Emim]OH; Homogeneous Catalyst; Green Approach; 3,4-Dihydropyrano[c]chromene